A Matlab/Simulink Model for Multi-Scroll Chaotic Attractors - Kaya, Duygu; Turk, Mustafa (Ieee, 2015)
In this study, the number of chaotic attractors only accepts as input parameter and a Matlab/Simulink model is developed for 5-10 multi-scroll chaotic attractor behaviors. In the model, as possible as simple Simulink blocks used and contained within MATLAB compiled by HDL Coder were seen to be the creation of VHDL code. In the model, to create the number of single and double attractors, employed with different parameters in the same structure two type non-linear resistance model was created. In the model, using a voltage-controlled switch, the number of different chaotic attractors has been to the creation. The advantage of the model, six different multi-chaotic attractor behaviors can be exhibited with a single structure. When considered from this point of view, it can be mentioned that the model's dynamic structure.
Çoklu Kaotik Çekerler Için Bir Matlab/Simulink Modeli
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: chaos; Matlab/Simulink; Multi-Scroll Chaotic Attractors